2022
DOI: 10.3389/fpsyg.2022.862626
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Media News Overload on Social Media News Avoidance and Filtering: Moderating Effect of Media Literacy

Abstract: In the present era of information technology, people tend to seek out news to enhance their current knowledge and awareness and to gain literacy. The reliance on seeking out news and relevant information has become very necessary to accomplish personal and organizational objectives. The present study has undertaken an inquiry to investigate the impact of social media news overload on news avoidance and news filtering with the mediating and moderating mechanisms of the need for news and media literacy, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
0
3
0
1
Order By: Relevance
“…Inappropriate online news dissemination or recommendations result in biased and irrelevant information and can be detrimental to individual users because it interferes with their understanding of the information (Chopra & Wallace, 2003). Individual users find it difficult to understand the news the sharer receives and will avoid it (Tian, 2022). Apart from that, the results show that social friendship does not affect understanding because online news that is shared or obtained from social friendship is not something to be understood but as a tool to strengthen connectedness (Bondad-Brown et al, 2012;Hampton et al, 2011;Kim & Lee, 2018).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Inappropriate online news dissemination or recommendations result in biased and irrelevant information and can be detrimental to individual users because it interferes with their understanding of the information (Chopra & Wallace, 2003). Individual users find it difficult to understand the news the sharer receives and will avoid it (Tian, 2022). Apart from that, the results show that social friendship does not affect understanding because online news that is shared or obtained from social friendship is not something to be understood but as a tool to strengthen connectedness (Bondad-Brown et al, 2012;Hampton et al, 2011;Kim & Lee, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…The higher the quality of the information provided by the web/site as a source of information, the more they will use the website to access online news. Individual users as online news readers only need trustworthy and credible news (Tian, 2022). Information quality from online news provided by news websites can be used to predict web usage (Chiu & Huang, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Çin'de 358 sosyal medya kullanıcısı ile gerçekleştirilen araştırma, bireylerin sosyal medyada aşırı haber yüküne maruz kaldıklarını ve bu durumdan kurtulmak için haber aramaktan kaçınabildiğini ya da kendileri için yorucu olan haberleri filtreleme eğilimine girdiklerini ortaya koymuştur (Tian, 2022).…”
Section: Bulgular Ve Yorumunclassified
“…1.1 Review of Literature Tian (2022) conducted study on the effects of social media news overload on news avoidance and news filtering behaviour using the requirement for news and media literacy as a mediating and moderating mechanism. The study found that if people were overloaded with news, they stop looking for that altogether or became engrossed in the tiresome task of weeding out the news that was actually useful.…”
Section: Introductionmentioning
confidence: 99%